2010
DOI: 10.3324/haematol.2010.031468
|View full text |Cite
|
Sign up to set email alerts
|

Continued improvement in myocardial T2* over two years of deferasirox therapy in  -thalassemia major patients with cardiac iron overload

Abstract: BackgroundThe efficacy of cardiac iron chelation in transfusion-dependent patients has been demonstrated in one-year prospective trials. Since normalization of cardiac T2* takes several years, the efficacy and safety of deferasirox was assessed for two years in patients with β-thalassemia major in the cardiac sub-study of the EPIC trial. Design and MethodsEligible patients with myocardial T2* greater than 5 to less than 20 ms received deferasirox, with the primary endpoint being the change in T2* from baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 21 publications
(32 reference statements)
6
57
0
2
Order By: Relevance
“…The extension period of the study was not designed to detect differences between the chelation regimens since patients were no longer randomized. The relative improvement in myocardial T2* from baseline in deferasirox patients was consistent with previous 2-year data from the single-armed EPIC cardiac substudy [18] and also indicated a greater improvement in myocardial T2* in the second year compared with the first. Variation in the rate of improvement between CORDELIA and trials based on other chelation strategies, including DFO and/or deferiprone, should be interpreted with caution as a result of differences in study design and patient populations [9,10,12,19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The extension period of the study was not designed to detect differences between the chelation regimens since patients were no longer randomized. The relative improvement in myocardial T2* from baseline in deferasirox patients was consistent with previous 2-year data from the single-armed EPIC cardiac substudy [18] and also indicated a greater improvement in myocardial T2* in the second year compared with the first. Variation in the rate of improvement between CORDELIA and trials based on other chelation strategies, including DFO and/or deferiprone, should be interpreted with caution as a result of differences in study design and patient populations [9,10,12,19].…”
Section: Discussionsupporting
confidence: 87%
“…There was a steady reduction in mT2* in patients with baseline LIC !15 mg Fe/g dw, consistent with other deferasirox studies over 2 years [15,18]. Patient numbers in the LIC <15 mg Fe/g dw DFO arm were too low for meaningful interpretation of differences, but in patients with G mean myocardial T2* <10 ms at baseline, G mean levels improved to above the clinically relevant threshold of 10 ms at month 24 for both treatment groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…22,23 Therefore, MRI has become the de facto standard for all recent clinical trials on iron chelation and the clinical standard of care in major thalassemia centers. 10,24 In clinical practice, validation is more important than calibration. For inaccessible organs such as the pituitary and pancreas glands, absolute iron concentrations may never be derived; however, the R2 and R2* values associated with glandular dysfunction and destruction are under investigation.…”
Section: Experimental Calibration Versus Validationmentioning
confidence: 99%
“…1,2 Although all available iron chelators have demonstrated efficacy in removing cardiac iron, prospective data beyond one year of treatment are rather limited. [3][4][5][6][7][8][9][10] As removal of cardiac iron may take several years, it is imperative to assess the effects of longer-term iron chelation therapy in the context of efficacy, safety and cardiac function. Results from the EPIC (Evaluation of Patients' Iron Chelation with Exjade ® ) cardiac substudy have shown continued, significant reduction of cardiac iron, as assessed by T2* cardiovascular magnetic resonance (CMR) over two years of deferasirox treatment in patients with mild-to-moderate (T2* 10 to <20 ms) and severe (T2* >5 to <10 ms) myocardial siderosis.…”
Section: Introductionmentioning
confidence: 99%